Energy confinement in the torsatron Uragan-3M during the RF-heating mode - Pashnev, V.K.; Burchenko, P.Ya.; Lozin, A.V.; Kotsubanov, V.D.; Kulaga, A.Ye.; Krasnyj, V.V.; Mironov, Yu.K.; Nikol’skii, I.K.; Petrushenya, A.A.; Romanov, V.S.; Sitnikov, D.A.; Sorokovoy, Ed.L.; et al. (Вопросы атомной науки и техники, 2008)
Energy confinement time of plasma in torsatron U-3M was measured both during quasi-stationary stady of RF-discharge and after RF-power cut-off. Power absorbed by plasma in the confinement region was estimated. A mechanism which explain the plasma density behavior in the confinement region is proposed.